2021
DOI: 10.3390/life11101097
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T Cell Vaccines and a Cytomegalovirus-Based Vector Approach

Abstract: The twentieth century witnessed a huge expansion in the number of vaccines used with great success in combating diseases, especially the ones caused by viral and bacterial pathogens. Despite this, several major public health threats, such as HIV, tuberculosis, malaria, and cancer, still pose an enormous humanitarian and economic burden. As vaccines based on the induction of protective, neutralizing antibodies have not managed to effectively combat these diseases, in recent decades, the focus has increasingly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 131 publications
0
1
0
1
Order By: Relevance
“…In addition, the upregulation of AHSA1 expression is also associated with the development of hepatocellular carcinoma; it has been shown to promote the proliferation and metastasis of hepatocellular carcinoma in vivo by recruiting ERK1/2 and contributing to the phosphorylation and inactivation of CALD1, which is associated with poor prognosis in those with hepatocellular carcinoma ( 33 ). Previous studies have shown that CD8+ T cells are one of key combatants of tumor cells ( 34 - 36 ). However, when infiltrating cancer tissues, they are generally in a dysfunctional state, which known as T-cell exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the upregulation of AHSA1 expression is also associated with the development of hepatocellular carcinoma; it has been shown to promote the proliferation and metastasis of hepatocellular carcinoma in vivo by recruiting ERK1/2 and contributing to the phosphorylation and inactivation of CALD1, which is associated with poor prognosis in those with hepatocellular carcinoma ( 33 ). Previous studies have shown that CD8+ T cells are one of key combatants of tumor cells ( 34 - 36 ). However, when infiltrating cancer tissues, they are generally in a dysfunctional state, which known as T-cell exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…Darüber hinaus weist HCMV eine Reihe von Eigenschaften auf, die es als viralen Impfvektor interessant macht [3,4]. Dazu zählen das ausgeprägte CD8-T-zellbasierte Immungedächtnis, welches die lebenslang persistierende HCMV-Infektion hervorruft [5], aber auch das breite Wirtszellspektrum, sowie die Größe und Manipulierbarkeit des Virusgenoms. HCMV besitzt mit ca.…”
unclassified